Translation in Medieval and Reformation Norway: A History of Stories or the Story of History - Rasmussen, Elizabeth (Meta, 2004)
AbstractThree major events marked medieval Norwegian literary production, style, and language: the introduction of Christianity, the Black Death, and the Reformation. Foreign material in translation was pivotal to the transition between the pagan Viking Era and the Christian Middle Ages and to the passage from Catholicism to Lutheranism in the 16th century. Lack of translation and literary production following the Black Death also had an impact.Translation in a medieval and Renaissance context must be understood as transfer of knowledge, the crossing of linguistic and cultural borders. The translated texts helped introduce and consolidate the social conventions promoted by the new religion. The distinction between story and history faded. Religious and devotional material preceded the secular court literature from the French-speaking territories. Hagiographic material ran parallel to heroic tales: all genres helped illustrate the virtues of Christian life and social organization and needed only minor adaptation for a Norse audience. The pagan literary conventions blended with those of the imported material and resulted in a distinct Norse literary style.The systematic encounter with other gave rise to a new perception of self. The largely anonymous translators contributed to the inclusion of other in self, to the assimilation of foreign cultural values and concepts.